2018
DOI: 10.15184/aqy.2018.147
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological LiDAR in Italy: enhancing research with publicly accessible data

Abstract: Recent changes to the availability and accessibility of LiDAR data in Italy have greatly expanded the potential for their exploration by members of the general public. Further promotion of this fact and how to engage with such data could prove to be of significant value to both archaeologists and other interested parties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Those systems are capable of achieving much higher accuracies with laser footprint diameters on the surface in the order of a few decimeters [ 14 ]. Often airborne LiDAR data are periodically acquired and made available to the public free of charge by local authorities [ 7 , 18 ]. During the last years, the use of airborne LiDAR for detecting and documenting historical remains has thus been investigated by several authors.…”
Section: Introductionmentioning
confidence: 99%
“…Those systems are capable of achieving much higher accuracies with laser footprint diameters on the surface in the order of a few decimeters [ 14 ]. Often airborne LiDAR data are periodically acquired and made available to the public free of charge by local authorities [ 7 , 18 ]. During the last years, the use of airborne LiDAR for detecting and documenting historical remains has thus been investigated by several authors.…”
Section: Introductionmentioning
confidence: 99%
“…The RVT software has been developed by a research group from the Slovenian Academy of Sciences and Arts, in a project managed by Žiga Kokalj. At the time, we relied on the studies carried out by Massini et al [16] to locate the structures of a medieval fortification in Basilicata (Italy) hidden under a thick blanket of forest; the Samnitic Hillforts of Civitella (Longano, Italy); the archaic and Hellenistic urban centre of Satricum (Lazio) analysed using SAGA functions [17], or the record of archaeological traces in the Roman limes of Dacia in Porolissum (Romania) carried out by Roman et al [18].…”
Section: Materials and Methods Usedmentioning
confidence: 99%
“…However, Tapete and Cigna [28] (pp. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] have shown that the joint use of multiple SAR images at different time points in the same study area can reduce speckle by providing images of greater clarity than treating them individually. This reduction is carried out through the co-register function, which implies the creation of a stack of images, with one referent, and the rest-subordinate.…”
Section: Sar Sources Techniques Usedmentioning
confidence: 99%
“…En Grèce, l'absence de couverture nationale LiDAR librement accessible, comme on en trouve dans d'autres pays européens 22 , est clairement un frein au développement de recherches archéologiques non-invasives dans le pays. Dans le cas présent, l'acquisition de données pour appuyer la recherche sur deux sites différents a permis de mieux documenter et de mieux comprendre les sites archéologiques en question, mais aussi les paysages qui les entourent.…”
Section: Conclusion Et Perspectivesunclassified